On generalized inverses of singular matrix pencils - Röbenack, Klaus; Reinschke, Kurt (Zielona Góra: Uniwersytet Zielonogórski)
Linear time-invariant networks are modelled by linear differential-algebraic equations with constant coefficients. These equations can be represented by a matrix pencil. Many publications on this subject are restricted to regular matrix pencils. In particular, the influence of the Weierstrass structure of a regular pencil on the poles of its inverse is well known. In this paper we investigate singular matrix pencils. The relations between the Kronecker structure of a singular matrix pencil and the multiplicity of poles at zero of the Moore?Penrose inverse and the Drazin inverse of the rational matrix are investigated. We present example networks whose circuit equations yield singular matrix pencils.
Keywords: matrix pencils; Kronecker indices; Moore?Penrose inverse; Drazin inverse; linear networks